Toward a Cure: Does Host Immunity Play a Role? - Jielin Zhang (American Society for Microbiology, 2017)
ABSTRACT Three decades of research on human immunodeficiency virus (HIV) and AIDS reveal that the human body has developed through evolution a genome immune system embodying epigenetic regulation against pathogenic nucleic acid invasion. In HIV infection, this epigenetic regulation plays a cardinal role in HIV RNA production that silences HIV transcription at a molecular (RNA) level, controls viral load at a cellular (biological) level, and governs the viremic stage of AIDS at the clinical (patient) level. Even though the human genome is largely similar among humans and HIV is a single viral species, human hosts show significant differences in viral RNA levels, ranging from cell to organ to individual and expressed as elite controllers, posttreatment controllers, and patients with AIDS. These are signature biomarkers of typical epigenetic regulation whose importance has been shunted aside by interpreting all of AIDS pathogenesis by the known properties of innate and adaptive immunity. We propose that harnessing the host genome immune system, defined as epigenetic immunity, against HIV infection will lead toward a cure.